Problems and Prospects of SME Financing in Bangladesh - Chowdhury, Md. Shahnur Azad; Azam, Md Kazi Golam; Islam, Serajul (Asian Business Review, 2013)
The present study is conducted to analyze the potential of SMEs in the economy of Bangladesh. Data were collected from 100 SME units by using simple random technique. A structural questionnaire was developed to get the responses from different SME units in the country. For Bangladesh SMEs have assumed special significance for poverty reduction programmes and potential contribution to the overall industrial and economic growth. Some of the constraints related SME financing are identified and some pointers for the future are provided through the study.
Keywords: SME; GDP; Economy